E-Stamp : "no licking, no sticking, just clicking" - Glazer, Rashi; Anderson, Rain; Caltaiano, Marc; Finke, Junko; Wong, Edmund (London : SAGE Publications Ltd, 2017)
In 1999, E-Stamp, a Palo Alto-based company, was racing to become the first approved by the United States Postal Service to sell postage over the Internet. E-Stamp was the first company to develop the technology to allow customers to buy postage over the Internet, and the first to pass through each stage of the USPS approval process. Upon approval, E-Stamp would be only the fifth company ever to secure the right to sell U.S. postage and the first to be granted permission to sell postage over the Internet. E-Stamps goal was to establish its brand as being synonymous with the on-line postage category. Its business plan had four objectives: build the category, acquire customers quickly and cost effectively, encourage recurring usage, and cross-sell additional products and services to increase the revenue per customer. An aggressive partnership strategy would enable the company to cost-effectively acquire customers and generate incremental revenue. However, one of the greatest challenges would be to convince customers to adopt a new platform for postage delivery.
Originally published in Glazer, R., Anderson, R., Caltaiano, M., Finke, J., & Wong, E. (2007). E-Stamp: "No licking. No sticking. Just clicking." The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; E-Stamp.; Strategic planning; Electronic commerce; Postage stamps